Pelatihan Modifikasi Kukis Sagu di Kampung Gwinjaya, Bonggo Timur Sarmi, Provinsi Papua - Suyono, Ign. Joko; Gunaedi, Tri; Busup, Ronald (Bakti Hayati: Jurnal Pengabdian Indonesia, 2024)
This community service activity aims to improve the quality and quantity of sago cookie products in a modified form from its first form in the village-owned business unit "Makmur Jaya" Giwinjaya, East Bonggo District, Sarmi Regency, especially in the Sago Cookie business unit. The improvement in quality will be tried to be trained to make sago cookies with a volume of 10 cm and a slightly different taste from the first product plus a little salty, while the quantity will be tried to make sago cookies on a small industrial scale by adding oven equipment and baking sheets so that sago cookies will be obtained in larger quantities compared to the old product. This activity also involved students from the Food Technology study program, Cenderawasih University as a form of integration with the Merdeka Belajar curriculum. The results achieved, members of the sago cookie business unit group have been able to improve the quality and quantity of sago cookie products as seen from the size of the product and the amount produced with the results of the average level of preference of respondents showing a level of preference for the products produced.